The Judicial Power as an Institutional Tool for Citizen Participation within the Framework of the Theory of Deliberative Democracy - Cabral, Pablo Octavio (2019)
The goal of this work is to address, from the conceptual framework of theories on “deliberative democracy”, the role played by the Judicial Power, being an integral part of the State, as the institutionalized field of deliberation for making collective decisions. In order to do this I will start by analyzing, from a legal-institutional perspective, the way in which the National Constitution of Argentina distributes the functions of the State and how it divides the competences to decide on the Public Thing. Furthermore, I will analyze which are the degrees of deliberation and of citizen participation (direct or indirect) in each portion of the constituted power. Then, I will develop my intuition about the way Justice operates as an institutional form of citizen participation within a Social State of Law, comparing such proposal with the opinion of authors that highlight the countermajoritarian nature of the Judicial Power. I will present some representative cases of the intervention of the Judicial Power in the making of institutionalized public decisions, generated by the action of minorities with little or no political representation and in which, after a deliberative practice, government measures that gave a positive response to the proposals of the actors were ordered.